Individual Indicators of Time Perception among Acrobats of Different Sports Qualifications (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Results of researches lasting for many years and dealing with the problem of forming professionally-applied physical education of students of naval colleges mastering swimming specialties based on the four models methods being worked out by the researchers are presented in the paper.